Phormidium phycoerythrin forms hexamers in crystals: a crystallographic study. Issue 8 (1st August 2015) - Sonani, Ravi Raghav; Sharma, Mahima; Gupta, Gagan Deep; Kumar, Vinay; Madamwar, Datta
<x xml:space="preserve">Abstract</x> The crystallographic analysis of a marine cyanobacterium (Phormidium sp. A09DM) phycoerythrin (PE) that shows distinct sequence features compared with known PE structures from cyanobacteria and red algae is reported. Phormidium PE was crystallized using the sitting‐drop vapour‐diffusion method with ammonium sulfate as a precipitant. Diffraction data were collected on the protein crystallography beamline at the Indus‐2 synchrotron. The crystals diffracted to about 2.1 Å resolution at 100 K. The crystals, with an apparent hexagonal morphology, belonged to space group P1, with unit‐cell parameters a = 108.3, b = 108.4 Å, c = 116.6 Å, α = 78.94, β = 82.50, γ = 60.34°. The molecular‐replacement solution confirmed the presence of 12 αβ monomers in the P1 cell. The Phormidium PE elutes as an (αβ)3 trimer of αβ monomers from a molecular‐sieve column and exists as [(αβ)3]2 hexamers in the crystal lattice. Unlike red algal PE proteins, the hexamers of Phormidium PE do not form higher‐order structures in the crystals. The existence of only one characteristic visual absorption band at 564 nm suggests the presence of phycoerythrobilin chromophores, and the absence of any other types of bilins, in the Phormidium PE assembly.